2015
DOI: 10.7603/s40680-015-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis knowledge level of the women living in the city of kirikkale

Abstract: Amaç: Osteoporoz postmenopozal kadınlarda sık görülen önemli bir halk sağlığı sorunudur. Çalış-mamızın amacı Kırıkkale ilinde yaşayan kadınların osteoporoz bilgi düzeyini ve bilgi düzeyi ile yaş ve eğitim düzeyi arasındaki ilişkiyi araştırmaktır. Yöntem OSTEOPOROSIS KNOWLEDGE LEVEL OF THE WOMEN LIVING IN THE CITY OF KIRIKKALE RESEARCH ARTICLE ABSTRACTPurpose: Osteoporosis is an important common public health problem among postmenopausal women. Purpose of this study is to research osteoporosis awareness level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…No difference was observed between the osteoporosis self-efficacy, age, and education levels among the participants in the present study. A previous study conducted with women in Turkey showed a linear relation between the years of education and osteoporosis self-efficacy level (23). In addition, age was found to be related to the osteoporosis knowledge and osteoporosis self-efficacy of women (24).…”
Section: Discussionmentioning
confidence: 69%
“…No difference was observed between the osteoporosis self-efficacy, age, and education levels among the participants in the present study. A previous study conducted with women in Turkey showed a linear relation between the years of education and osteoporosis self-efficacy level (23). In addition, age was found to be related to the osteoporosis knowledge and osteoporosis self-efficacy of women (24).…”
Section: Discussionmentioning
confidence: 69%
“…In a study conducted with 419 women between the ages of 19 and 60 with different education levels, it was reported that the osteoporosis self-efficacy level was low [ 18 ]. Arslan et al found that the OSES scores of the participants were low in their study, which included 236 individuals over the age of 35, 53.4% female and 34.7% literate, who applied to the bone densitometry unit of a hospital [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that physically inactive individuals have a higher incidence of osteoporosis and related complications [ 24 ]. In the study of Arslan et al, it is shown that the higher the education level, the higher the osteoporosis self-efficacy-efficacy level [ 19 ]. When the results are examined, it is thought that people with high osteoporosis self-efficacy can develop fracture prevention behaviors, and their quality of life is affected by this situation.…”
Section: Discussionmentioning
confidence: 99%